Isomeric D‐π‐D Dopant‐Free Hole Transport Materials: Effect of the Substitution Position and Heteroatom on the Performance of Perovskite Solar Cells. Issue 25 (1st July 2022) - Liang, Yongpeng; Wu, Nan; Zhang, Xianfu; Ghadari, Rahim; Liu, Xuepeng; Guo, Fuling; Dai, Songyuan
Abstract: A series of facile small‐molecular D‐π‐D HTMs with dibenzofuran or dibenzothiophene as π‐bridge, and the triarylamine groups as peripheral arms was designed and prepared. The impact of the varied substitution position of triarylamine groups on the π‐bridge and heteroatomic effect on the molecular and device properties are extensively studied. All the molecules exhibit suitable energy alignment of the HOMO with the valence band of perovskite. 3, 7‐molecules showed red‐shift spectra compared to that of 4, 6 and 2, 8‐counterparts, indicating the better conjugation. Due to the better hole extraction and conductivity of 3, 7‐molecules because of enhanced conjugation, which exhibits relatively best power conversion efficiency. 4, 6‐substituents exhibit inferior device performance due to the broken conjugation of 4, 6‐position and bad film‐forming ability. Moreover, the O‐based HTMs exhibit relatively better device performance when the terminal groups are located on 3, 7‐position due to enhanced hole extraction ability. However, the heteroatom effect of 4, 6‐substituent is contrary with 3, 7‐counterpart due to the opposite conductivity change trend. Abstract : The 3, 7‐substituents exhibit enhanced conjugation and better hole extraction ability, leading to better performance in perovskite solar cells compared with other HTMs. 4, 6‐substituents exhibit inferior device performance due to the broken conjugation of 4, 6‐position and bad film‐forming ability. The heteroatom exhibits different effect when the side arm located different position on the bridges. All the devices with developed molecules exhibit better stability than spiro‐OMeTAD because no dopants are used.